Pengembangan Business Process Improvement Sistem Informasi Rekam Medis Pasien Rawat Jalan Bidan Praktik Mandiri Menggunakan Zachman Framework (Studi Pada Ikatan Bidan Indonesia Cabang Kabupaten Trenggalek) - Dias Aditya; Yusi Tyroni Mursityo; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Nowadays medical data management is done manually has been made to be automatic with information system to accelerate work process of health practitioner in obtaining medical data. Midwife Practice Mandiri is currently performing medical records of patients using manual methods so that business processes that are running currently less than optimal. The development of information systems technology today should be utilized by midwives to be able to help maximize performance on their services. To create a system in this research used Enterprise Architecture Zachman Framework and Business Process Improvement method in order to analyze in advance the existing business process for further improvement. This research will use 3 perspectives from 6 perspectives that exist in Zachman Framework. After that performed the implementation of a prototype Medical Record Information System Bidan Practice Independent which is a representation of the proposed business process. The tests were performed using black-box testing method, and fit / gap analysis. The result of this research is a medical record information system that can assist midwife performance in speeding up service and making recap of service result. Benefits provided that will speed up the nets of existing business processes by implementing an information system.